Clinical approach to prostatic diseases in the dog. Issue 6 (2nd May 2019) - Cunto, Marco; Mariani, Elisa; Anicito Guido, Eleonora; Ballotta, Giulia; Zambelli, Daniele
Contents: In small animal practice, prostatic diseases are increasingly encountered. All dogs may experience prostatic disease, but particular care should be addressed to breeding dogs, in which prostatic affection may lead to decrease in semen quality and fertility. The most common prostatic disease is the benign prostatic hyperplasia (BPH) followed by prostatitis, prostatic neoplasia and prostate squamous metaplasia. These diseases do not have pathognomonic symptoms, therefore, making a correct diagnosis may not be easy. An accurate clinical examination and a correct diagnostic protocol are essential in order to begin the most appropriate treatment, and also to do a good prophylaxis where it is possible. BPH therapy is usually recommended when mild‐severe signs are present or if symptoms disturb the patient. New therapeutic approaches, both medical and surgical, allow to maintain fertility in most animals with prostatic disorders. Prostate cancer is relatively infrequent. Elective therapy is the surgical one, but it is considered palliative and can result in important post‐operative complications. The aim of this paper is to lay down the most appropriate diagnostic process describing the aetiologies of prostatic disease, their symptoms, the right investigative tools and therapy.